The Lévy Laplacian - Feller, M. N. (Mikhail Naumovich), 1928- (Cambridge tracts in mathematics ;, 2005)
The Lévy Laplacian is an infinite-dimensional generalization of the well-known classical Laplacian. The theory has become well-developed in recent years and this book is the first systematic treatment. With an extensive bibliography, the work will be valued by those working in functional analysis, partial differential equations and probability theory.